Pengembangan Bahan Ajar Laju Reaksi Berbasis STEM-PBL pada Mata Kuliah Dasar Ilmu Kimia - Mutiara Agustina Nst.; Dwy Puspita Sari; Ani Sutiani; Mutia Ardila (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to develop teaching materials on reaction rates based on the STEM-Problem Based Learning (STEM-PBL) approach and to assess their validity and practicality, ensuring they are suitable for use in a basic chemistry course. The study employed the Research and Development (R&D) method using the Plomp model, which encompasses the stages of preliminary investigation, design, product development, evaluation, and revision. The research involved three expert validators and 30 students from the Chemistry Education Study Program. Data collection instruments included validation sheets and practicality questionnaires. Validation results indicated that the teaching materials fell into the